Peran Keterikatan Dosen Dalam Meningkatkan Kinerja Perguruan Tinggi Swasta Aceh Selama Covid-19 - Muhammad Zainal Abidin; Fadli Syahputra; Faridah Faridah (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
Researchers investigated the relationship between employee engagement, meeting applications, leadership and organization performance. This research combines the social media usage model that has been developed previously with the engagement model by William Khan. This research uses quantitative methods with a population of private tertiary institutions in Aceh Province and a total sample of 280 lecturers who were taken by purposive sampling technique based on certain criteria. The results of the structural equation model analysis show that the performance of private universities in Aceh can be influenced by employee engagement, application meetings, and leadership.